KEBUGARAN KARDIORESPIRATORIK PADA LANSIA YANG MENGIKUTI DAN TIDAK MENGIKUTI SENAM DENGAN 6-MINUTE WALKING TEST (6-MWT) DI SURABAYA - Siagian, Martha; Lataima , Nurmawati S; Revita, Natalia Christin Tiara (Journal of Nursing and Midwifery Sciences, 2023)
The process of aging results in changes in the cardiovascular and respiratory systems. Gymnastics can improve physical health and help the body work more efficiently. The purpose of this study was to analyze the effect of exercise on the fitness cardiorespiratory elderly. The design of this study is pre-experimental with the study design of Static Group comparison. The population was 28 elderly using purposive sampling and becoming respondents. The independent variable was gymnastics elderly and the dependent variable is the fitness cardiorespiratory. Instruments to measure fitness using 6-Minute Walking Test. Descriptive statistical analysis of the results, the percentage proportion of the majority (71%) of respondents who do not follow gymnastics fitness cardiorespiratory have less, and most (79%) of respondents who follow gymnastics cardiorespiratory elderly have good fitness. There are significant differences in the SMEs' cardiorespiratory fitness exercise with those who did not follow gymnastics as evidenced by the results of the statistical test p = 0.008. It was concluded that exercise helps improve and maintain fitness cardiorespiratory.